The clinical outcomes of selective and spontaneous fetal reduction of twins to a singleton pregnancy in the first trimester: a retrospective study of 10 years - Chao Wang; Fei Tang; Bing Song; Guanjian Li; Qiong Xing; Yunxia Cao (BMC, 2022)
Abstract Background Singleton pregnancy is encouraged to reduce pregnancy complications. In addition to single embryo transfer (SET), selective and spontaneous fetal reduction (SEFR and SPFR) can also achieve singleton pregnancies. After SEFR or SPFR, an inanimate fetus remains in the uterus. It is unclear whether the inanimate fetus would adversely affect another fetus or the mother. Previous studies have focused on the differences between pre- and post-reduction. However, studies focusing on the influence of SEFR and SPFR on the remaining fetal development and maintenance of pregnancy are rare. Methods Materials from 5922 patients whose embryo transfer dates ranged from March 2011 to January 2021 were collected. Both the SEFR group (n = 390) and SPFR group (n = 865) had double embryos transferred (DET) and got twin pregnancies, but subsequent selective or spontaneous fetal reduction occurred. The SET group (n = 4667) had only one embryo transferred. All were singleton pregnancies on the 65th day after embryo transfer. Clinical outcomes, including pregnancy outcomes, pregnancy complications, and newborn outcomes, were compared among the three groups. Results After adjusting for age, infertility duration, types of infertility, states of embryos, body mass index, and factors affecting SET or DET decisions, multivariate regression analysis revealed that SEFR increased the risk of miscarriage (OR 2.368, 95% CI 1.423-3.939) and preterm birth (OR 1.515, 95% CI 1.114-2.060), and reduced the gestational age (βeta -0.342, 95% CI -0.544- -0.140). SPFR increased the risk of gestational diabetes mellitus (GDM) (OR 1.657, 95% CI 1.215-2.261), preterm premature rupture of membranes (PPROM) (OR 1.649, 95% CI 1.057-2.574), and abnormal amniotic fluid volume (OR 1.687, 95% CI 1.075-2.648). Both SEFR and SPFR were associated with reduced live birth rate (OR 0.522, 95% CI 0.330-0.825; OR 0.671, 95% CI 0.459-0.981), newborn birth weight (βeta -177.412, 95% CI -235.115--119.709; βeta -42.165, 95% CI -83.104--1.226) as well as an increased risk of low-birth-weight newborns (OR 2.222, 95% CI 1.490-3.313; OR 1.510, 95% CI 1.092-2.087). Conclusions DET with subsequent fetal reduction was related to poor clinical outcomes. We recommend that DET with subsequent fetal reduction should only be considered as a rescue method for multiple pregnancy patients with potential complications, and SET is more advisable.